Pre-lacteal feeding practice and associated factors among mothers having children aged less than six months in Dilla town, Southern Ethiopia - Anteneh Gashaw; Haymanot Mitku (BMC Pediatrics, 2024)
Abstract Background Pre-lacteal feeding, the introduction of liquids or non-breast milk foods before establishing regular breastfeeding, poses significant risks to newborns, depriving them of vital nutrients and the protective benefits of colostrum while exposing them to infection hazards. Despite breast milk being a renewable and comprehensive source of infant nutrition for the first six months of life, prevalent in many low income country are pre-lacteal feeds such as honey, sugar-water, jiggery water, castor oil, and goat’s milk. These practices, widespread in such regions, carry potential risks of infection and aspiration. The objective of this study is to assess the prevalence of pre-lacteal feeding and identify associated factors among mothers with children under six months in Dilla Town, Southern Ethiopia. Method A community-based cross-sectional study took place in Dilla town, southern Ethiopia, spanning from June 20 to August 20, 2022. The study included a total of 372 participants, selected through simple random sampling for kebele and systematic random sampling for individual participants. Data was collected using interviewer-administered structured questionnaires and subsequently coded, entered, cleaned, and edited using SPSS version 23.0 software. The presentation of data utilized tables and figures, followed by a logistic regression analysis to identify potential factors associated with pre-lacteal feeding. The significance level was set at a p-value less than 0.05 for the final model. Result The prevalence of pre-lacteal feeding practice was 176 (47.3%) in the study area and having no maternal education (AOR = 3.68, 95% CI; [1.01–5.84] colostrum avoidance (AOR = 4.20, 95% CI; [2.03–6.86] and lack of breast feeding counseling (AOR = 2.00, 95% CI; 1.40–2.57), were factors associated with pre-lacteal feeding practices. Conclusion and recommendation Pre-lacteal feeding practice among mothers of children aged less than 6 months in Dilla town was found to be higher than the national prevalence. No formal education, colostrum avoidance, lack of breastfeeding counseling, were factors associated with pre-lacteal feeding practices. So awareness creation activities on the risks of PLF (pre-lacteal feeding) and improving breastfeeding counseling targeted to all mothers and care givers including their families within the study area is vital.